Desenvolvimento de pão “sourdough” sem glúten a partir de culturas starters - Sabino, Adrielle (2015)
With this growing demand for gluten-free products, there is the need for innovations and development in bakery products. The absence of gluten in bread is a very important factor for people with celiac disease caused by intolerance to gluten. The natural fermentation "sourdough" employed by several people since ancient times, it is quite feasible and possible to produce breads with higher nutritional quality. Furthermore, the "sourdough" aid in the digestion and bioavailability of some nutrients during fermentation since breakdown occurs some molecules, which facilitates the absorption process. In this study we analyzed the breads produced mixtures through seven "sourdough '' with the use of selected cultures of Lactobacillus species and the Lactobacillus rhamnosus and Bifidobacterium bifidum and Saccharomyces cerevisiae yeast, demonstrating that the use of natural yeast can be very satisfactory both for large-scale reproduction and for small productions. For the production of "sourdough" held analytical determinations of pH and titratable acidity. They were evaluated texture parameters (firmness and elasticity) and the specific volume of the seven formulations developed in sensory analysis were selected three formulations of bread for color evaluation, flavor, texture, flavor and overall impression, as well as purchase intent. Checking the results of analyzes, it can be said that the bread of the seven mixtures prepared with standardized formulations with rice flour and "sourdough", achieved good results. To sense, the results were well received where two formulations were the ones that stood out showing that they present viable for commercialization and consumption.